2022
DOI: 10.34172/aim.2022.96
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Survival and Prognostic Factors of Breast Cancer

Abstract: Background: Breast cancer survival rate is an important index for assessment of treatment effect in reducing the mortality. Weaimed to determine the fifteen-year survival rate for breast cancer at a referral center in Iran and its correlated factors. Methods: This survival study enrolled patients with breast cancer who referred to Motamed Cancer Institute (MCI) from 1998 to2016. The survival rate was calculated using the Kaplan-Meier method. The relationship of demographic, clinical and therapeuticfactors with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The multivariate analysis revealed that CD105 expression was an independent predictor for MFS, BMFS, and OS in our BCPs (p = 0.0003, p = 0.0006, and 0.0001, respectively) (Table 5). Unfortunately, lymph nodes status was not an independent prognostic factor for MFS, like other authors found (Weissenbacher et al, 2010;Bitencourt et al, 2020;Olfatbakhsh et al, 2022). This result may be attributed to the selection of early primary breast tumors and/or the small cohort size.…”
Section: Multivariate Analysismentioning
confidence: 74%
“…The multivariate analysis revealed that CD105 expression was an independent predictor for MFS, BMFS, and OS in our BCPs (p = 0.0003, p = 0.0006, and 0.0001, respectively) (Table 5). Unfortunately, lymph nodes status was not an independent prognostic factor for MFS, like other authors found (Weissenbacher et al, 2010;Bitencourt et al, 2020;Olfatbakhsh et al, 2022). This result may be attributed to the selection of early primary breast tumors and/or the small cohort size.…”
Section: Multivariate Analysismentioning
confidence: 74%